Implementasi Digital Assurance dalam Peningkatan Mutu Pendidikan di Sastra Inggris IAIN Surakarta - Akhmad Anwar Dani; Ari Hikmawati; Fathan Fathan (UHN IGB Sugriwa Denpasar, 2019)
Educational quality assurance is an important part of the education system, its function is to ensure that the education process goes according to plan and is able to achieve the goals effectively and efficiently. The implementation of Digital Assurance in the English Literature Department of Surakarta IAIN is one of the innovative steps in the quality assurance process at Surakarta IAIN. This paper will describe the transformation process that occurs in the implementation of Digital Assurance. Data obtained from interviews and documentation studies. The analysis carried out concluded that the transformation process of quality assurance based on Digital Assurance in the Department of English Literature used a Top-Down pattern. Transformation is supported by leadership factors and strong commitment, adequate human resource support and a conducive organizational ecosystem.